Pembelajaran Berbasis Proyek: Hasil Belajar Optimal Berbasis Pengalaman - Sulistiyowati, Tri Indah; Nuraina, Elva; Handayani, Siti Nur (Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Sumatera Utara, 2025)
This study aims to improve student learning outcomes through the implementation of the Project Based Learning model in the topic of the system and mechanism of fund collection in Islamic banking at SMK Negeri 5 Madiun. This research is a classroom action research (CAR) conducted in two cycles with 13 students from the XI Islamic Banking class as the subjects. Data were collected through formative tests and observation sheets to assess students' understanding and observe the learning activities. The results showed an improvement in learning outcomes in each cycle. In cycle 1, the learning completeness percentage was 69%, while in cycle 2, it increased to 92%. The implementation of the Project Based Learning model had a positive impact on student engagement, reflected in the improvement of learning products and group collaboration skills. Although there were challenges regarding students' communication skills and self-confidence during presentations, this study indicates that the Project Based Learning model is effective in enhancing student learning outcomes and can be used as an alternative active learning approach relevant to 21st-century needs.